Hubungan Tingkat Aktivitas Fisik dengan Ketebalan Lemak Viseral pada Usia Remaja - P. Harsuno, Nalendra; I. S. Wungouw, Herlina; Poli, Hedison (Green Publisher Indonesia, 2025)
Accumulation of visceral fat can become a health issue for instance central obesity. Globally, it has reached milestone of >890 million cases and is expected to continue increasing. Meanwhile, physical activity is considered to have a significant impact on body weight, especially during adolescence. With technological and transportation advancements, people tend to engage in less physical activity and adopt a sedentary lifestyle. As proven by Indonesia Basic Health Research (Riskesdas) in 2018 there are 50,4% of adolescents aged 15-19 years out of 67.140 study participants were categorized with low physical activity levels. This study aimed to determine a relationship between physical activity level and visceral fat thickness in adolescents. This study used analytic observational study with cross-sectional approach. Data collection was conducted through primary means using questionnaire for physical activity and ultrasonography (USG) for visceral fat thickness. Samples were selected with purposive sampling, with 87 respondents matching the inclusion and exclusion criteria. Based on collected data, the level of physical activity among respondents was predominantly in heavy category, with 54 participants (62,1%). The mean value of visceral fat thickness was (6.52 ± 2.27). Statistical analysis showed a p-value = 0,335 (p> 0,05) and r = -0,105 using Pearson’s correlation test. There is no significant relationship between physical activity level and visceral fat thickness in adolescents.